Motivational-emotional and cognitive factors of sports preparedness of young basketball players - Liudmyla Frolova; Andrii Tymofeev; Irina Khomenko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to establish the degree of influence of motivational-emotional and cognitive factors on the athletic preparedness of young basketball players, taking into account the exercise of the dominant and subdominant hands. Material & Methods: young basketball players of 12-13 years old were investigated. They carried out testing of physical and technical readiness, determined motivation, personal and situational anxiety, stress resistance, memory, attention, and also the effectiveness of competitive activity. Results: data of physical and technical readiness, competitive activity, cognitive abilities and motivational-emotional state of young basketball players of 12-13 years of preliminary basic training were analyzed and the factors correlated. A significant amount of reliable links of sports readiness with the level of spatial-visual memory and anxiety is shown. Significantly less links of sports preparedness with the level of motivation and resistance to stress. Conclusions: It has been established that improving the athletic fitness of young basketball players aged 12-13 years can be influenced by increased motivation to achieve success, an increase in the level of spatial-visual memory, and a decrease in the level of situational and personal anxiety. At the same time, to improve technical mastery and increase the efficiency of competitive activity, the stress level of young athletes is of little importance.